TEXTUAL EQUIVALENCE IN TRANSLATION: COHESION FOUND IN BARACK OBAMA’S SPEECH “A NEW BIRTH OF FREEDOM” - Laia, Mirda Jadi (Universitas Nias Raya, 2024)
Translation is a process transfering language from source language to target language without changing the meaning with exhibiting qualities of equivalence. Textual equivalence refers to the equivalence in term of information and cohesion. Cohesion itself is a connection between one sentence to another. This research aimed at analyzing the textual equivalence in translation : Cohesion Found in Barack Obama’s Speech “A New Birth of Freedom”. Researcher used Baker’s theory to analyze the grammatical cohesion and lexical cohesion in this speech. The result of this research showed that there were two grammatical cohesion they are reference and conjunction, found in this research. The realization of textual equivalence in term of grammatical cohesion found that the text in source language are equivalently with the target language. However, in some cases the realization of textual equivalence in term of grammatical cohesion was found not equivalently in target language.